Influences of Fabrication Parameters on Natural Fiber Reinforced Polymer Composite (NFRPC) Material: A Review - Subbiah, Ram; Boopathi, Sampath; Sureshkumar, M.; Jeyakumar, M.; Kumar, R. Sanjeev (Materials science forum, 2022)
In the recent development of modern manufacturing industries, the metallic components have been replaced by natural polymer composite materials due to increasing the strength to weight ratio, developing eco-friendly components, and reducing the overall cost of the product. In this review article, the various research activities on the effects of various single-layer and multi-layer fibers, moisture contents, surface treatments methods, filler materials, and drilling processes on the Natural Fiber Reinforced Polymer Composite (NFRPC) characteristics have been illustrated. The research opportunities for future developments in NFRPC materials have been extracted from the literature.